Global Financial Stability Report, April 2010 : Meeting New Challenges to Stability and Building a Safer System. (Global Financial Stability Report; Global Financial Stability Report ;, 2010)
Risks to global financial stability have eased as the economic recovery has gained steam. But policies are needed to reduce sovereign vulnerabilities, ensure a smooth deleveraging process, and complete the regulatory agenda. The April 2010 Global Financial Stability Report examines systemic risk and the redesign of financial regulation; the role of central counterparties in making over-the-counter derivatives safer; and the effects of the expansion of global liquidity on receiving economies.